Impact of Transformational Leadership and Work Motivation on Performance with Work Ethic Mediation - Oni Fakhrizni; Eka Yudhyani; Evi Kurniasari (Journal La Bisecoman, 2024)
The study aims to determine the effect of transformational leadership and work motivation on employee performance with work ethic as a mediator variable at PT Bank Mandiri (Persero) Tbk Samarinda Branch. This study uses a quantitative approach with 136 employees of PT Bank Mandiri (Persero) Tbk - Samarinda Branch. The analytical tool used in this research is the SmartPLS version 3.2.9 application. The data analysis process in this study was carried out with the measurement model (outer model), structural model (inner model) and hypothesis testing using Bootstrapping. The results of this study indicate that transformational leadership (X1) has a positive and significant effect on work ethic (Z), work motivation (X2) has a positive and significant effect on work ethic (Z), transformational leadership (X1) has a positive and significant effect on employee performance (Y), work motivation (X2) has a positive and significant effect on employee performance (Y), work ethic (Z) has a positive and significant effect on employee performance (Y), this study also proves that work ethic (Z) is able to mediate the effect of transformational leadership (X1) on employee performance (Y), and work ethic (Z) is able to mediate the effect of work motivation (X2) on employee performance (Y).